Business models for the Blockchain: An empirical analysis - Nitin Upadhyay (Digital Business, 2024)
Business models of industries and ventures enabled by new and emerging technologies are under-developed and fragmented. The blockchain technology promises to disrupt the business models. However, the scholarly literature in blockchain research is only beginning to emerge, and the majority are focused on the technical aspect leaving aside the business model complexities for blockchain applications. This paper fills this gap and proposes a blockchain business model framework. The research utilizes a sequential exploratory research design (SERD), encompassing two key phases: an initial phase involving a literature review and interviews to delineate blockchain business model building blocks and types, followed by a subsequent survey to identify the most pertinent building blocks and types. The findings helped to formulate the framework, necessary building blocks, and block types specifically for the blockchain applications. Organizations can tailor their business model through various configuration options and mechanisms, considering the arrangement of block types within each block according to their significant score levels. By giving priority to those with scores above the block's average, organizations can evaluate the performance of their models and pinpoint areas for enhancement. The proposed framework can be considered as a reference point for developing business models for blockchain applications.
Keywords: 650; Applications; Blockchain; Business ecosystems; Business model; Business model innovation; Configuration